2018
DOI: 10.1136/bmjsem-2018-000357
|View full text |Cite|
|
Sign up to set email alerts
|

Study of the measurement and predictive validity of the Functional Movement Screen

Abstract: ObjectiveThe aim of the study was to evaluate the reported measurement capabilities and predictive validity of the Functional Movement Screen (FMS) for injury.MethodsThis was a prospective observational longitudinal study of 24 male footballers from a single team in England, alongside analysis of an existing database over one season (September 2015–May 2016). A preseason FMS was carried out with scores recorded by an experienced assessor and derived, retrospectively, from the three-dimensional movement data th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
(15 reference statements)
0
9
0
1
Order By: Relevance
“…Results from study 1 identified that the FMS scale and scoring criteria, in its current form, did not demonstrate the basic properties needed to provide an accurate measure of movement, injury risk or any of the other reported capabilities of the FMS 6. Similar results were observed in study 2, as the FMS thresholds used to predict injury, whether scores were determined by a real-time assessment or an objective assessment of 3D movements, did not predict injury.…”
Section: What Did I Find?mentioning
confidence: 69%
“…Results from study 1 identified that the FMS scale and scoring criteria, in its current form, did not demonstrate the basic properties needed to provide an accurate measure of movement, injury risk or any of the other reported capabilities of the FMS 6. Similar results were observed in study 2, as the FMS thresholds used to predict injury, whether scores were determined by a real-time assessment or an objective assessment of 3D movements, did not predict injury.…”
Section: What Did I Find?mentioning
confidence: 69%
“…subjective reports by the patient and measurements or specialist clinical tests performed by the physiotherapist. Subjective reporting can be subject to recall bias (26) and clinical scales or orthopaedic tests lack sensitivity and speci city (27,28). Clinical decision-making processes based on these are therefore likely to be prone to error.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval was granted and a pre-existing dataset collected as part of a prospective observational longitudinal study (set up in accordance with the consensus statement for data collection and injury reporting in football) was used in this study 7 11. Additional personal training activities not planned by the team’s coaching or fitness staff were recorded within the database alongside measures of fitness and workload.…”
Section: Methodsmentioning
confidence: 99%